2700-1800 BC: the bell beaker question: origin and diffusion during the third millennium BC - Cardoso, João Luís (2022)
The weak genetic influence of the Central European regions on Beaker populations within Portuguese territory means that the latter, whether due to their remote geographical location or, above all, their earlier chronology, did not receive any input from this diffusion, thus affirming that they are the direct descendants of their Neolithic ancestors.